1997
DOI: 10.1103/physrevd.55.1985
|View full text |Cite
|
Sign up to set email alerts
|

Global structure of Robinson-Trautman radiative space-times with cosmological constant

Abstract: Robinson-Trautman radiative space-times of Petrov type II with a nonvanishing cosmological constant ⌳ and mass parameter mϾ0 are studied using analytical methods. They are shown to approach the corresponding spherically symmetric Schwarzschild-de Sitter or Schwarzschild-anti-de Sitter solution at large retarded times. Their global structure is analyzed, and it is demonstrated that the smoothness of the extension of the metrics across the horizon, as compared with the case ⌳ϭ0, can increase for ⌳Ͼ0 and decrease… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
39
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 33 publications
9
39
1
Order By: Relevance
“…32,33 The results proving the global existence and convergence of the solutions of the Robinson-Trautman equation can be taken over from the previous studies since Λ does not explicitly enter this equation. We have shown that, starting with arbitrary, smooth initial data at u = u 0 (see Fig.…”
Section: On Physical Interpretation Of Non-twisting Type N Solutions mentioning
confidence: 99%
“…32,33 The results proving the global existence and convergence of the solutions of the Robinson-Trautman equation can be taken over from the previous studies since Λ does not explicitly enter this equation. We have shown that, starting with arbitrary, smooth initial data at u = u 0 (see Fig.…”
Section: On Physical Interpretation Of Non-twisting Type N Solutions mentioning
confidence: 99%
“…Extensions across the "Schwarzschild-like" future event horizon can only be made with a finite order of smoothness. These results were generalized in [7,8] to Robinson-Trautman vacuum spacetimes with cosmological constant. These cosmological solutions settle down to a Schwarzschild-(anti-)de Sitter solution at large times u.…”
Section: Introductionmentioning
confidence: 99%
“…Extensions across such a "Schwarzschild-like" future event horizon are only of a finite order of smoothness. These results were later extended to cover the presence of a cosmological constant which naturally modifies the asymptotic behavior and the solutions tend to Schwarzschild-(anti-)de Sitter cases [8,9]. Finally, the Chruściel-Singleton analysis was used for RobinsonTrautman spacetimes admitting additionally pure radiation [10,11], where the asymptotic state is described by spherically symmetric Vaidya-(anti-)de Sitter metric.…”
Section: Introductionmentioning
confidence: 99%